Comparison of Antibacterial Effectiveness of Arabica Coffee Bean Extract (Coffea arabica L.) Roasted and Non-Roasted Against Bacteria Enterococcus faecalis - Shirley Adriana; Phimatra Jaya Putra; Verawati Sinaga (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2023)
Background: Dental caries that are not handled properly cause cavities and open the dental pulp so that it becomes a pathway for microorganisms to enter the root canals. The most common microorganisms found in root canal infections are Enterococcus faecalis. Arabica coffee beans have bioactive compounds such as alkaloids, saponins, and tannins, which inhibit the growth of bacteria. This study aimed to compare the antibacterial effectiveness of roasted and non-roasted Arabica coffee bean extracts against bacteria Enterococcus faecalis. Methods: This study was an in vitro experimental study. This research uses culture Enterococcus faecalis, which were divided into 10 groups (2 control groups, 4 treatment groups of roasted coffee beans, and 4 groups of non-roasted coffee beans). Inhibition zone diameter analysis was carried out with the help of SPSS using univariate and bivariate. Results: Non-roasted Arabica coffee bean extract showed better effectiveness in inhibiting bacterial growth Enterococcus faecalis, along with increasing the concentration of the extract. Conclusion: Non-roasted Arabica coffee bean extract is more effective as an antibacterial against the bacteria Enterococcus faecalis compared to roasted Arabica coffee bean extract.